Velikomoravsko-panonsko besedišče v makedonskih biblijskih besedilih od 12. do 15. stoletja - Nikolovski, Gjoko (Studia Historica Slovenica, 2016)
The article deals with the presence of Moravian and Pannonian vocabulary in Macedonian Biblical texts from the 12th to the 15th century. Moravian and Pannonian vocabulary in the Macedonian Biblical text occurs after the return of Cyril and Methodius- students to the Macedonian and Bulgarian territory. By comparing the presence of the Moravian and Pannonian vocabulary in canonical monuments of Old Church Slavonic (9th-11th century) and in the Macedonian Biblical texts from the 12th to the 15th century is created a broader view of the creation of Old Church Slavonic as the first literary language of the Slavs.
Keywords: besedišče; Makedonija; stara cerkvena slovanščina; svetopisemska besedila